2020
DOI: 10.4235/agmr.20.0030
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Body Mass Index and Their Associations with Mortality among Older Adults in Korea: Analysis of the Korean Longitudinal Study of Aging

Abstract: Weight change is an important risk factor for mortality. The association of weight change with mortality is frequently shown as a reverse J-shaped curve. 1,2) Weight loss in overweight or obese people and weight gain in underweight people have beneficial effects on health. 1) However studies have reported conflicting results depending on ethnicity and age groups. While some studies reported that weight loss and weight gain increased mortality, 3,4) others found no associations. 5) Instead of using baseline bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…There were 12 studies [47][48][49][50][51][52][53][54][55][56][57][58] (13 cohorts; 187,866 participants) with general populations (Table S3). Of these, seven cohorts were in East Asia, and three cohorts in each Europe and North America.…”
Section: General Populationsmentioning
confidence: 99%
“…There were 12 studies [47][48][49][50][51][52][53][54][55][56][57][58] (13 cohorts; 187,866 participants) with general populations (Table S3). Of these, seven cohorts were in East Asia, and three cohorts in each Europe and North America.…”
Section: General Populationsmentioning
confidence: 99%
“…Furthermore, Korean cohort studies showed that Korean adults tended to lose weight with age during longitudinal follow-up. 24,28 Therefore, there may be a limitation to assess the association between weight loss and development of ACRN in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Fifth, the difference in AD risk according to late-life BMI may have been underestimated. In another study that followed 10-year mortality among Koreans aged 65 years or older, the lower the baseline BMI, the higher the mortality rate 43 which implied a higher chance of dying before AD develops. Finally, our study could not prove a causal relationship between late-life BMI and the incidence of AD because many possible confounding factors affecting the incidence of AD that cannot be identified in this database were not considered.…”
Section: Discussionmentioning
confidence: 99%